Pengaruh Model Pembelajaran Demonstrasi Terhadap Peningkatan Kemampuan Hasil Belajar Bahasa Indonesia Tentang Teks Deskripsi - Mohammad Lukmanul Hakim; Sri Devi; Alif Suprayit (Jurnal Ilmiah Wahana Pendidikan, 2023)
Demonstration Learning Method is a very effective teaching method to assist students in finding answers to questions such as: how to make it? What material is it made of? How do I set it up? How does the process work? Demonstration method is a way of presenting lessons by demonstrating a process of events. The demonstration method is usually applied using teaching aids such as miniature objects, pictures, laboratory equipment and others. Therefore, the Demonstration Learning Model needs to be applied so that the ability to learn Indonesian about descriptive text can increase.